2020
DOI: 10.1186/s40945-019-0071-6
|View full text |Cite
|
Sign up to set email alerts
|

Electrical interferential current stimulation versus electrical acupuncture in management of hemiplegic shoulder pain and disability following ischemic stroke-a randomized clinical trial

Abstract: Background: Hemiplegic Shoulder Pain (HSP) is among common complications occurring after stroke leading to disability. This study was conducted to compare the effects of electrical Interferential Current stimulation (IFC) and Electrical Acupuncture (EAC) on pain intensity, range of motion, and functional ability in patients with HSP and also comparing the two modalities regarding improvement of above indices. Methods: In this randomized clinical trial, 46 patients with HSP caused by ischemic stroke were recrui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 42 publications
(62 reference statements)
0
35
0
Order By: Relevance
“…In addition, combining IFT with manual therapy and exercises gets better results in decreasing pain, improving function, and increasing pain-free range of motion compared to instructions alone in patients with acromioplasty [31]. Furthermore, Eslamian et al [26] reported that both IFT and electrical acupuncture improved short-term functional status, enhanced motion, and reduced pain in hemiplegic patients. Although acupuncture had greater pain control, IFT was more effective in increasing function and active range of motion.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, combining IFT with manual therapy and exercises gets better results in decreasing pain, improving function, and increasing pain-free range of motion compared to instructions alone in patients with acromioplasty [31]. Furthermore, Eslamian et al [26] reported that both IFT and electrical acupuncture improved short-term functional status, enhanced motion, and reduced pain in hemiplegic patients. Although acupuncture had greater pain control, IFT was more effective in increasing function and active range of motion.…”
Section: Discussionmentioning
confidence: 99%
“…[46] And there was substantial evidence to support the validity and reliability of the NRS, FPS-R, and McGi pain questionnaire as a measure of pain intensity. [47,48] Secondary outcomes were upper limb motor function assessed by Fugl-Meyer assessment scale for upper limb (FMA-U), [49] ADL assessed by Barthel index (BI) [50] or modified Barthel index (MBI), [51] and adverse events (AEs). The total score of FMA-U is 66 points, the higher the total score, the upper limb motor function is better.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…Record the patient's heart rate and tolerance time before and after exercise test termination. 5 Laboratory examination: Before and after treatment, the patient will take venous blood to check fasting blood glucose, blood insulin, blood lipids, blood cholesterol, high-sensitivity c-reactive protein, the oral glucose tolerance test (OGTT)2h blood glucose and insulin, and follow the formula [HOMA-IR=fasting blood glucose×fasting insulin÷ 22.5] Calculate the homeostatic model insulin resistance index (HOMA-IR). The higher the value, the lower the insulin sensitivity.…”
Section: End Of Exercise Test Heart Rate and Tolerance Timementioning
confidence: 99%